Porphyra yezoensis Sauces Fermented With Lactic Acid Bacteria: Fermentation Properties, Flavor Profile, and Evaluation of Antioxidant Capacity in vitro - Yang, Jie; Gao, Tengqi; Ge, Feng; Sun, Hao; Cui, Zihang; Wei, Zhen; Wang, Shujun; Show, Pau Loke; Tao, Yang; Wang, Wenbin (Frontiers in Nutrition, 2022)
The demand for Lianyungang sandwich seaweed (Porphyra yezoensis) product has risen in recent years. The process of product slicing technology has created a huge number of scraps that are not being utilized effectively. Three LAB strains were used to ferment Porphyra yezoensis sauce in this study, including Lactobacillus fermentum, Lactobacillus casei, Streptococcus thermophilus, and the mixed strains (1:1:1 v/v). The fermentation characteristics, antioxidant capacity in vitro, sensory evaluation, and flavoring substances of fermented P. yezoensis sauce were analyzed. After 21 days of fermentation, all LAB strains grew well in P. yezoensis, with protease activity increased to 6.6, 9.24, 5.06, and 5.5 U/mL, respectively. The flavor of P. yezoensis sauce fermented with L. casei and L. fermentum is satisfactory. On this premise, GC-MS was used to investigate the changes in gustatory compounds in P. yezoensis sauce fermented with L. casei and L. fermentum. In general, 42 and 41 volatile flavor chemicals were identified after the fermentation of L. casei and L. fermentum. Furthermore, the fermented P. yezoensis sauce possessed greater DPPH scavenging activity and ferric-reducing ability power (FRAP) than the unfermented P. yezoensis. Overall, the flavor and taste of P. yezoensis fermented by L. casei are superior.